Optimasi Suhu Annealing Gen Blaz Dari Bakteri Methicillin-Resistant Staphylococcus Aureus (MRSA) Pada Peralatan Medis: Optimization Annealing Temperature Gene blaZ of Bacterial Methicillin-resistant Staphylococcus aureus (MRSA) in Medical Equipment - Listiani, Lia; Dhanti, Kurnia Ritma; Kurniawan, Kurniawan; Widodo, Oei Stefani Yuanita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Methicillin-resistant Staphylococcus aureus is a strain of S. aureus bacteria that is resistant to methicillin-type penicillins. MRSA bacteria can cause nosocomial infections, which can be spread through medical equipment. One of the genes that encodes the resistance trait of S. aureus is the blaZ gene. The detection of the blaZ gene requires optimizing the annealing temperature of the primer used to obtain the optimal PCR band. This study aims to optimize the annealing temperature for the amplification of the blaZ gene DNA from Methicillin-resistant Staphylococcus aureus (MRSA) bacteria on medical devices. The method used in this study used a kit for bacterial extraction and Polymerase Chain Reaction(PCR). The results of the blaZ gene DNA amplification in all samples showed clear bands at temperatures of 52.0°C, 54.2°C, 58.7°C, 61.8°C, and 64.0°C; no smears were formed, and the electrophoretic visualization results on the PCR product showed the results of bands that were according to the target, namely 173 bp. The most optimal annealing temperature for amplification of the blaZ gene in MRSA bacteria from hospital medical equipment is 61.8°C.